FAKTOR PENGARUH TERHADAP KETERSEDIAAN SEPTICTANKDAN SAMBUNGAN SEWERAGE SYSTEM PERMUKIMAN PINGGIRAN KALI, KEL. DANGIN PURI, DENPASAR - swastika, dewa gede; Dwipayanti, Utami (ARCHIVE OF COMMUNITY HEALTH, 2012)
At dangin puri, sub distric of denpasar timur, most of communities that live at streamside do not have basic sanitation facilities such as septic tank or sewerage system connection, thus the wastewater is directly ? owed into the stream. This study was aimed to identify the risk factors that in? uence septic tank ownership and sewerage facilities utilization by streamside communities in dangin puri. Some risk factors included in this study were knowledge, education, income, occupant density, house ownership, house position towards the stream, distance of toilet to stream and backyard size. The study was a cross-sectional study where the samples were families that live at the streamside in dangin puri. Data were analyzed using logistic regression in order to identify the most in? uencing factor of septic tank ownership and sewerage facilities utilization.        The results illustrate that only one factor that proves the correlation that is distance of toilet to stream (or=8,733; p=0.006; ?=0.05), whereas other factors do not role as risk factors. The communities with short distance of toilet to stream have a potential of 8.733 times to not have septic tank and sewerage system connection compare to others. The data analysis also demonstrates that there are other factors other than that included in this study with more in? uencing roles. The regulation and the participation of all stakeholders such as communities and private sectors will improve the coverage of basic sanitation in order to achieve the target of MDGs.
Keywords: Risk Factors, Septic Tank, Sewerage System